Methods of supporting training and post-exercise recovery in women practising fitness and men practising bodybuilding: Supporting of training in amateur athletes - Boguszewski, Dariusz (Journal of Education, Health and Sport, 2022)
Introduction. The aim of this study was to characterize physiotherapeutic methods applied in supporting training and biological regeneration of amateur athletes (women practising fitness and men practising bodybuilding). Materials and methods. 115 participated in the survey, 45 women practising fitness and 70 men practising bodybuilding. The author’s survey constituted the study tool. Differences were calculated using the chi-squared and t-Student test for independent groups, assuming p≤0.05 as the minimum significance level. Results. Regular use of physiotherapy treatments supporting trainings and post-exercise regeneration was declared by 48 (42%) of the studied athletes (44% women 40% men). Regular perform of stretching exercises was declared by The most frequently used treatment indicated by women and men was sauna. Regular perform of stretching exercises after training was declared by 68 (59%) of the studied people. The most examined amateur athletes (66%) declared using diet supplementary (51% women and 75% men). The most frequently used dietary supplement were vitamins and minerals in women and proteins in men Conclusions. Less than 50% examined amateur athletes use physiotherapeutic support of training regularly. Application of physiotherapeutic support of training in amateur sports should be promoted by coaches, physiotherapist and medical staff. The most frequently used physiotherapeutic treatments are the ones which are easily accessible (sauna, massage). Nonetheless, their effectiveness has been scientifically proven.